2020
DOI: 10.1073/pnas.1920062117
|View full text |Cite
|
Sign up to set email alerts
|

Connectivity and plasticity determine collagen network fracture

Abstract: Collagen forms the structural scaffold of connective tissues in all mammals. Tissues are remarkably resistant against mechanical deformations because collagen molecules hierarchically self-assemble in fibrous networks that stiffen with increasing strain. Nevertheless, collagen networks do fracture when tissues are overloaded or subject to pathological conditions such as aneurysms. Prior studies of the role of collagen in tissue fracture have mainly focused on tendons, which contain highly aligned bundles of co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
34
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(40 citation statements)
references
References 64 publications
5
34
1
Order By: Relevance
“…To study cell migration in mechanically unrestrained microenvironments, we created in vivo mimetics by using specially designed sample chambers to encapsulate cells in 3D gels formed by Collagen I polymer networks. This resulted in microenvironments with stiffnesses on the order of 1 kPa (Bordeleau et al, 2017; Burla et al, 2020). The chambers enable imaging with our meSPIM and ASLM light-sheet microscopes, both of which exhibit near-isotropic spatial resolution of approximately 300 nm (Dean et al, 2015; Welf et al, 2016), which enables spatially unbiased 3D computational analysis of the morphology and membrane-associated signals (Driscoll et al, 2019).…”
Section: Resultsmentioning
confidence: 99%
“…To study cell migration in mechanically unrestrained microenvironments, we created in vivo mimetics by using specially designed sample chambers to encapsulate cells in 3D gels formed by Collagen I polymer networks. This resulted in microenvironments with stiffnesses on the order of 1 kPa (Bordeleau et al, 2017; Burla et al, 2020). The chambers enable imaging with our meSPIM and ASLM light-sheet microscopes, both of which exhibit near-isotropic spatial resolution of approximately 300 nm (Dean et al, 2015; Welf et al, 2016), which enables spatially unbiased 3D computational analysis of the morphology and membrane-associated signals (Driscoll et al, 2019).…”
Section: Resultsmentioning
confidence: 99%
“…The building blocks that constitute this network range from stiff fibers 1 in paper or textiles, to semiflexible filaments in biological cells and tissues, [2][3][4] to flexible polymer chains in elastomers. 5 The network architecture is known to be important for the mechanical response and failure of these materials; 1,2,6,7 yet, most theoretical studies describe the failure response via continuum mechanics 8 or using a mean-field approach, 9 which ignore details of the network topology and neglect the role of structural disorder. Such models thus cannot provide a microscopic understanding of the failure process.…”
Section: Introductionmentioning
confidence: 99%
“…RC tears cause shoulder pain and disability and increase health care system costs worldwide, but surgical repair success rate remains inadequate (Randelli et al, 2012), resulting in worse clinical outcomes (Haque & Pal Singh, 2018). A detailed understanding of the under- that were not evaluated in this study (e.g., collagen microstructure organization (Burla et al, 2020;Seo et al, 2020) may also have played a role in conferring mechanical strength beyond the first two postoperative weeks. Indeed, tendon tensile strength may be further influenced by factors such as constituent collagen type, collagen fiber alignment, and cross-linking, as well as proteoglycan composition (Buckley et al, 2013;Burla et al, 2020;Lake et al, 2010;Seo et al, 2020).…”
Section: Discussionmentioning
confidence: 94%
“…A detailed understanding of the under- that were not evaluated in this study (e.g., collagen microstructure organization (Burla et al, 2020;Seo et al, 2020) may also have played a role in conferring mechanical strength beyond the first two postoperative weeks. Indeed, tendon tensile strength may be further influenced by factors such as constituent collagen type, collagen fiber alignment, and cross-linking, as well as proteoglycan composition (Buckley et al, 2013;Burla et al, 2020;Lake et al, 2010;Seo et al, 2020). In studying the regional collagen composition and alignment of the SSP, Buckley et al reported that collagen I was present throughout the tendon of human cadaveric SSP samples and likely provided durability and strength to the tendon, whereas collagen II was most prevalent near the SSP insertion site at the greater tuberosity, suggesting that higher proportions of collagen II contributed to the ability of the SSP to adapt to compressive loading (Buckley et al, 2013).…”
Section: Discussionmentioning
confidence: 99%